2020
DOI: 10.1080/13876988.2020.1762076
|View full text |Cite
|
Sign up to set email alerts
|

Politicizing the Use of Glyphosate in Europe: Comparing Policy Issue Linkage across Advocacy Organizations and Countries

Abstract: The European Citizens' Initiative enables advocacy organizations to place policy issues on the political agenda. Which frames did advocacy organizations use to mobilize the support of citizens for the initiative on banning glyphosate and to politicize this issue? The article shows for France, Germany, Italy, Portugal, and Spain that some advocacy organizations linked the issue of glyphosate to the related issue of genetically modified organisms (GMOs) and/or referred to the controversial Monsanto company in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 46 publications
(49 reference statements)
0
15
0
1
Order By: Relevance
“…The intense and heated techno‐scientific and political debate, led mainly by social‐environmental groups, on the presence of transgenes in Mexican maize landraces, 18,49,50 that prevented the legal cultivation of transgenic maize in Mexico, served to promote the questioning of the environmental impacts and health risks of glyphosate, 17,18,57 after IARC classified glyphosate a possible carcinogen in 2015, 15 the same category in which red meat and coffee are included. The speed at which the Mexican government decreed a total ban of glyphosate as of January 2024, published in the Diario Oficial de la Federación on December 31, 2020, 23 attracted worldwide attention.…”
Section: Glyphosate Banmentioning
confidence: 99%
See 2 more Smart Citations
“…The intense and heated techno‐scientific and political debate, led mainly by social‐environmental groups, on the presence of transgenes in Mexican maize landraces, 18,49,50 that prevented the legal cultivation of transgenic maize in Mexico, served to promote the questioning of the environmental impacts and health risks of glyphosate, 17,18,57 after IARC classified glyphosate a possible carcinogen in 2015, 15 the same category in which red meat and coffee are included. The speed at which the Mexican government decreed a total ban of glyphosate as of January 2024, published in the Diario Oficial de la Federación on December 31, 2020, 23 attracted worldwide attention.…”
Section: Glyphosate Banmentioning
confidence: 99%
“…There is a long list (more than 150) of active ingredients of pesticides used in Mexico with environmental impacts and health risks similar or more severe than those of glyphosate 26 . Among the most controversial pesticides in Mexico are aldrin/dieldrin, DDT, endosulfan, heptachlor, lindane, and paraquat 61 ; however, political and social pressure has fallen only on glyphosate 17,86 . Endosulfan is carcinogenic and is prohibited in the European Union, but in Mexico it is only classified as possibly teratogenic and its conditional importation has been allowed since 2012; the possible carcinogens aldrin/dieldrin, DDT and lindane are banned in 23, 26 and 11 countries, respectively, since 1970, and although their use is restricted in Mexico, they have been imported since 1991 and 1993; the possible carcinogen heptachlor, which has been banned in 21 countries since 1994, does not have any importation, commercialization or use restrictions 39 ; while paraquat, the second most widely used herbicide in Mexico (27% of the herbicide market), 11,40 that increases the risk of developing Parkinsonʼs and DNA damage, 27 has no usage restrictions.…”
Section: Inconsistencies In the Use Of Dangerous Pesticides In Mexicomentioning
confidence: 99%
See 1 more Smart Citation
“…In general, the public debate represents one venue political actors use to try to influence policymaking (Leifeld, 2013 , 2020 ). Research has identified several ways in which participation in public debates may be influential: First, research on agenda-setting shows that emphasizing certain problem perceptions or policy solutions increases a topic’s likelihood to be discussed in legislative institutions (Baumgartner & Jones, 2009 ; Soroka & Wlezien, 2009 ; Tosun & Scherer, 2020 ; Tosun & Varone, 2020 ). Second, disseminating new information in public debates can lead to policy learning across political actors, which may trigger policy change (Leifeld & Brandenberger, 2019 ; Sabatier, 1998 ).…”
Section: Theoretical Approachmentioning
confidence: 99%
“…Thus, political actors participate in the debate in order to put forth their arguments or new information in order to trigger policy learning across coalitions. Second, through emphasising certain policy issues and solutions, but neglecting others, the public debate may have a profound impact on agenda-setting, making some policy issues and solutions more likely to be discussed in parliament than others [4,83,90,92]. Third, the public debate can shape public opinion [73], which may then affect politicians in their decision-making [84].…”
Section: Why Do Political Actors Reveal Their Policy Beliefs In the Pmentioning
confidence: 99%